Biochemistry of lactone formation in yeast and fungi and its utilisation for the production of flavour and fragrance compounds - Romero-Guido, Cynthia; Belo, Isabel; Ta, Thi Minh Ngoc; Cao-Hoang, Lan; Alchihab, Mohamed; Gomes, Nelma; Thonart, Philippe; Teixeira, Jose A; Destain, Jacqueline; Waché, Yves (Applied microbiology and biotechnology, 2011)
The consumers' demand for natural flavour and fragrances rises. To be natural, compounds have to result from the extraction of natural materials and/or to be transformed by natural means such as the use of enzymes or whole cells. Fungi are able to transform some fatty acids into lactones that can thus be natural. Although some parts of this subject have been reviewed several times, the present article proposes to review the different pathways utilised, the metabolic engineering strategies and some current concerns on the reactor application of the transformation including scaling up data. The main enzymatic steps are hydroxylation and β-oxidation in the traditional way, and lactone desaturation or Baeyer-Villiger oxidation. Although the pathway to produce γ-decalactone is rather well known, metabolic engineering strategies may result in significant improvements in the productivity. For the production of other lactones, a key step is the hydroxylation of fatty acids. Beside the biotransformation, increasing the production of the various lactones requires from biotechnologists to solve two main problems which are the toxicity of lactones toward the producing cell and the aeration of the emulsified reactor as the biochemical pathway is very sensitive to the level of available oxygen. The strategies employed to resolve these problems will be presented.